PERSONALITY AND LOW SELF-CONTROL AS CONTRIBUTING FACTORS FOR SCAM VICTIMIZATION: A CONCEPT PAPER - Murad, Fatin Adha (International Journal of Psychosocial Rehabilitation, 2020)
Commercial crimes such as scams are of great concerns especially to a society. Official reports indicate that there is a progressive increase in terms of amount of losses in frauds and scams every year. The worrying and escalating trends of scams are the rationale for this concept paper to exist. Following this, the current paper aims to review previous studies to explain why people are getting scammed from the victims’ psychological viewpoint. The present paper employs archival analysis as the main methodology to retrieve information from related journal articles. As such, previous journal articles were reviewed thoroughly to identify the contributing factors for scam victimizations. This paper includes two of the most researched factors in understanding commercial crime victimization – personality and self-control factors. In-depth understanding on victims’ psychological factors is imperative as it can provide substantial information for the development of psychosocial interventions for at-risk individuals.